(untitled) (Transport systems and technologies, 2021)
The paper deals with the justification of the need to use an asynchronous traction electric drive on the metro rolling stock. The advantages of using an asynchronous traction electric drive in comparison with a DC commutator motor drive are formulated. The characteristics of modern innovative metro rolling stock with asynchronous traction electric drive of domestic and foreign production are analyzed. Aspects of the choice of a variable frequency asynchronous traction electric drive for innovative rolling stock are formulated and the existing typical algorithm of such choice is given. The main reasons for the irrational choice of traction asynchronous electric drive for the metro rolling stock are considered and the consequences of such a choice are analyzed. It is proposed to improve the methodology for selecting a variable frequency traction asynchronous electric drive for the metro rolling stock in terms of such an important operational factor as the specific cost of electrical energy for traction. The rational parameters of the variable frequency asynchronous traction electric drive according to the proposed procedure for the specified characteristics of the metro rolling stock are specified. The reserves of energy savings for the given conditions due to the introduction of an asynchronous traction electric drive with rational parameters on the innovative rolling stock are determined. It is established that the efficiency factor of the asynchronous traction motor significantly affects the specific electric energy consumption for the metro rolling stock traction and operating costs.